Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Complex staged emplacement of a basaltic lava: The example of the July 1974 flow of Kīlauea - S. Biass; B. F. Houghton; E. W. Llewellin; K. C. Curran; T. Thordarson; T. R. Orr; C. E. Parcheta; P. Mouginis-Mark (Bulletin of Volcanology, 2025)
Basaltic lava flows can be highly destructive. Forecasting the future path and/or behavior of an active lava flow is challenging because topography is often poorly constrained and lava has a complex rheology and emplacement history. Preserved lavas are an important source of information which, combined with observations of active flows, underpins conceptual models of lava flow emplacement. However, the value of preserved lavas is limited because pre-eruptive topography and, thus, syn-eruptive lava flow geometry are usually not known. Here, we use tree-mold data to constrain pre-eruptive topography and syn-eruptive lava flow geometry of the July 1974 flow of Kīlauea (USA). Tree molds, which are formed after advancing lava encloses standing trees, preserve the lava inundation height and the final preserved thickness of lava. We used data from 282 tree molds to reconstruct the temporal and spatial evolution of the ~ 2.1 km-long July 1974 flow. The tree mold dataset yields a detailed dynamic picture of staged emplacement, separated by intervals of ponding. In some ponded areas, flow depth during emplacement (~ 5 m) was twice the preserved thickness of the final lava (2–3 m). Drainage of the ponds led to episodic surges in flow advancement, decoupled from fluctuations in vent discharge rate. We infer that the final breakout occurred after the cessation of fountaining. Such complex emplacement histories may be common for pāhoehoe lavas at Kīlauea and elsewhere in situations where the terrain is of variable slope, and/or where lava is temporarily perched and stored.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Fluorescent reporter transgenic mice for in vivo live imaging of angiogenesis and lymphangiogenesis - Susan J. Doh; Michael Yamakawa; Samuel M. Santosa; Mario Montana; Kai Guo; Joseph R. Sauer; Nicholas Curran; Kyu-Yeon Han; Charles Yu; Masatsugu Ema; Mark I. Rosenblatt; Jin-Hong Chang; et al. (Angiogenesis, 2018)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Late Pleistocene and early Holocene change in the Weddell Sea: a new climate record from the Patriot Hills, Ellsworth Mountains, West Antarctica - CHRIS TURNEY; CHRIS FOGWILL; TAS D. VAN OMMEN; ANDREW D. MOY; DAVID ETHERIDGE; MAURO RUBINO; MARK A. J. CURRAN; ANDRÉS RIVERA (Journal of Quaternary Science, 2013)
The transition from the late Pleistocene to the Holocene (30 000–5000 years ago) was a period of considerable climate variability, which has been associated with changes in deep water formation and the intensity of the Meridional Overturning Circulation. Although numerous records exist across the North Atlantic region, few Antarctic ice core records have been obtained from the south. Here we exploit the potential of upwelling ancient ice – so‐called blue ice areas (BIAs) – from the Patriot Hills in the Ellsworth Mountains to derive the first deuterium isotope record (δD) from continental Antarctica south of the Weddell Sea. Gas analysis and glaciological considerations provide a first relative chronology. Inferred temperature trends from the Patriot Hills BIA and snow pit suggest changing climate influences during the transition between the last glacial period and Holocene. Under modern conditions, the interplay between the Antarctic high‐pressure system and the Southern Annular Mode appears to play a significant role in controlling katabatic wind flow over the site while the BIA record suggests that greater sea ice extent during the last glacial period was a major control. Our results demonstrate the considerable potential of the Patriot Hills site for reconstructing past climate change in the south Atlantic region.

The incidence of unpleasant dreams after sub-anaesthetic ketamine - Mark Blagrove; Celia J. A. Morgan; H. Valerie Curran; Leslie Bromley; Brigitte Brandner (Psychopharmacology, 2009)

Long‐term reproductive behaviour of woody plants across seven Bornean forest types in the Gunung Palung National Park (Indonesia): suprannual synchrony, temporal productivity and fruiting diversity - Charles H. Cannon; Lisa M. Curran; Andrew J. Marshall; Mark Leighton (Ecology Letters, 2007)
For 68 months, we observed the reproductive behaviour of 7288 woody plants (172 figs, 1457 climbers and 5659 trees) spanning major soil and elevational gradients. Two 2–3 month community‐wide supra‐annual fruiting events were synchronized across five forest types, coinciding with ENSO events. At least 27 genera in 24 families restricted their reproduction to these events, which involved a substantial proportion of tree diversity (> 80% of phylogenetic diversity). During these events, mean reproductive levels (8.5%) represented an almost four‐fold increase compared with other months. These patterns indicate a strong behavioural advantage to this unusual reproductive behaviour. Montane forest experienced a single, separate fruiting peak while the peat swamp forest did not participate. Excluding these events, no temporal reproductive pattern was detectible, at either the landscape or forest type. These phenological patterns have major implications for the conservation of frugivore communities, with montane and swamp forests acting as ‘keystone’ forests.

Stratification by CARD15 variant genotype in a genome-wide search for inflammatory bowel disease susceptibility loci - Sarah H. Shaw; Jochen Hampe; Ray White; Christopher G. Mathew; Mark E. Curran; Stefan Schreiber (Human Genetics, 2003)

Gas space and oxygen exchange in roots of Avicennia marina (Forssk.) Vierh. var. australasica (Walp.) Moldenke ex N. C. Duke, the Grey Mangrove - William G. Allaway; Mark Curran; Lauren M. Hollington; Malcolm C. Ricketts; Nicholas J. Skelton (Wetlands Ecology and Management, 2001)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial: Reply - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)

Bahamian coral reefs yield evidence of a brief sea-level lowstand during the last interglacial - Brian White; H. Allen Curran; Mark A. Wilson (Carbonates and Evaporites, 1998)